2017
DOI: 10.1111/acps.12710
|View full text |Cite
|
Sign up to set email alerts
|

Affect lability predicts occurrence of suicidal ideation in bipolar patients: a two‐year prospective study

Abstract: Reducing affective lability could become a new therapeutic target of suicidal prevention in bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
4
11
0
Order By: Relevance
“…Findings of this report are consistent with the emerging literature linking anger to suicidality (Ducasse et al, 2017; Hogstedt et al, 2018; Start et al, 2019). In a recent report, Hogstedt et al (2018) found that likelihood of completed suicide and suicide attempts over a 35‐year follow‐up were 2.1 and 2.8 times higher in male Swedish conscripts with severe anger symptoms versus those with no anger symptoms at index visit.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Findings of this report are consistent with the emerging literature linking anger to suicidality (Ducasse et al, 2017; Hogstedt et al, 2018; Start et al, 2019). In a recent report, Hogstedt et al (2018) found that likelihood of completed suicide and suicide attempts over a 35‐year follow‐up were 2.1 and 2.8 times higher in male Swedish conscripts with severe anger symptoms versus those with no anger symptoms at index visit.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of this report are consistent with the emerging literature linking anger to suicidality (Ducasse et al, 2017;Hogstedt et al, 2018;Start et al, 2019). In a recent report, Hogstedt et al (2018) found that likelihood of completed suicide and suicide attempts over with fivefold greater likelihood of reporting SI (categorized as score ≥2 on suicide-related item of the 9-item Patient Health Questionnaire) (Start et al, 2019).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the rapid effects of antidepressants on emotional processing are seen in euthymic subjects as well as in those with depression; similarly, new treatments for BD, such as novel VGCC-acting drugs, could be screened in patients who have unstable mood but who do not have a formal diagnosis. Second, stabilisation of mood may be beneficial in its own right, above and beyond simply preventing clinical episodes of depression and mania, because mood instability independently predicts poor functional recovery in BD, and worse outcomes of various kinds [76,[82][83][84]. In addition, since mood instability often occurs before the onset of BD [85,86], such treatments might have a preventative role.…”
Section: Persistent Mood Instabilitymentioning
confidence: 99%
“…Moreover, the rapid effects of antidepressants on emotional processing are seen in euthymic subjects as well as in those with depression; similarly, new treatments for BD, such as novel VGCC-acting drugs, could be screened in patients who have unstable mood but who do not have a formal diagnosis. Second, stabilisation of mood may be beneficial in its own right, above and beyond simply preventing clinical episodes of depression and mania, because mood instability independently predicts poor functional recovery in BD, and worse outcomes of various kinds 76 , 82 , 83 , 84 . In addition, since mood instability often occurs before the onset of BD 85 , 86 , such treatments might have a preventative role.…”
Section: New Approaches To the Bipolar Phenotypementioning
confidence: 99%